Analysis of Soil Quality Index of mixed garden land use type on dry land in Blang Bintang sub-district, Aceh Besar district - Yusran Akbar; Umar H. A; Endiyani Endiyani; Sri Agustina; Irhami Irhami; Ika Rezvani; Irmayanti Irmayanti (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
This research was conducted by using a descriptive method based on the results of surveys and field observations and laboratory analysis. Field survey activities were carried out to obtain primary data in the form of general biophysical conditions of the area and physical and chemical characteristics of the soil obtained from observations and indicators of soil quality through soil analysis in the laboratory. Soil sampling points were determined using the purposive sampling method, namely points that have been determined in selected dry land areas in Blang Bintang District, Aceh Besar District. Soil sampling for analysis of chemical properties was carried out by drilling. Soil drilling was carried out to determine the thickness of the soil solum. Sampling was focused only on the top soil layer with a thickness of 0 - 20 cm. In mixed garden land use type (LUT) 5 - 6 sample points were taken which were then analyzed in the laboratory. From the data from the soil analysis, the fertility status of each type of land use will be determined. Field observations and sampling were carried out at each observation point (LUT) in the Blang Bintang District, Aceh Besar District.The soil characteristics and a large percentage of sand compared to the percentage of silt and clay. The low content of clay fraction in both lands affected the formation of soil aggregates. The position and composition of organic matter greatly determine the process of forming stability and distribution of aggregates. Sandy soil in mixed garden vegetation is difficult to absorb water and nutrients due to large grains and small surface area per unit weight. The soil which is dominated by the sand fraction is porous with high aeration pores. Smooth aeration properties can increase the oxidationof organic matter.